Migration, common property resources and environment degradation interlinkages in India's arid and semi-arid regions - Chopra, Kanchan; Gulati, S C (New Delhi Sage, 2001)
The book provides a fresh perspectives on the linkages between migration, poverty and environmantal degradation in India. They provide conclusive evidences concerning the impact of institutional changes on environmental upgradation and socio-economic impr
Keywords: Rural-Urban migration-India; Migration, Internal-India; Environmental degradation-India; Rights of property-India